The Contribution of ZIS (Zakat, Infaq, & Sadaqah) to Poverty Alleviation in North Sumatra Province - Batubara, Randi Hadamean; Utary Evy Cahyani (Islamic Economics Methodology, 2024)
This study aims to see the development of research on the topic of "Zakat Poverty" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Zakat Poverty" which comes from the Dimensions database with a total of 1,257 journal articles. Then, the data was processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Zakat Poverty" research development in the world. The results of the study found that in bibliometric author mapping the authors who published the most research on the theme of "Zakat Poverty" were Wildastuti; Tika; Johari; Fuadah; Beik; Irfan Syauqi; and Bahri; ES. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can become research lines with topics related to Zakat Poverty and Muslim Country, Zakat Poverty and Mustahik, Zakat Poverty and Effect, and Zakat Poverty and Cibest. Furthermore, the most used words are zakat, Muslim country, mustahik, effect, sustainable, Cibest, and SDGs.